Development of Emotion Cards as Emotional Literacy Media to Enhance Early Childhood Emotional Intelligence - Juliana Selvi; Abdul Saman; Azizah Amal; Herlina; Rusmayadi; Muhammad Akil Musi (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2026)
The limited availability of interactive emotional literacy materials in the classroom is a major obstacle to the development of emotional intelligence in early childhood. This study aims to develop Emotion Cards, a visual-digital learning tool that integrates illustrated emotion expression cards, QR code-based contextual animated videos, and an implementation guidebook for teachers. The study employed the 4D development model (Define, Design, Develop, Disseminate) with 4 teachers and 10 children aged 5–6 years at ABA III Paranga Kindergarten, selected through purposive sampling. Data were collected via expert validation sheets, teacher response questionnaires, and child emotional intelligence observation sheets, then analyzed using quantitative descriptive and nonparametric statistical methods. The expert validation results fell into the Valid category (mean 3.00), the teachers’ practicality assessment reached the Very Practical category (94.38%), and the Wilcoxon Signed-Rank test indicated a significant increase in children’s emotional intelligence (Asymp. Sig. = 0.04 < 0.05). These findings demonstrate that the Emotion Cards medium effectively stimulates the five dimensions of emotional intelligence: self-awareness, emotion regulation, self-motivation, empathy, and social skills. Further research is recommended to expand implementation across more diverse contexts and levels of early childhood education.